UPAYA MENINGKATKAN PARTISIPASI BELAJAR BAHASA INDONESIA MATERI TEKS PENGUMUMAN MELALUI METODE PROBLEM SOLVING PADA SISWA KELAS V SD NEGERI NO 100724 PADANG LANCAT - Syamsuraidah . (JURNAL MathEdu (Mathematic Education Journal), 2023)
This study aims to increase motivation to lear Indonesian Announcement Text Material. This type of research is Classroom Action Research (PTK) using two cycles. The subjects of this study were 12 students of fifth grade Students at SD Negeri No 100724. Data collection techniques in this study used tests, observation sheets and documentation. The instrument of this study is the syllabus, lesson plans. Data analysis used is descriptive data analysis. The results of the two-cycle study showed that there was student motivation increasing, which was in the first cycle the average student score was 60,19. Whereas in cycle II it showed a fairly high increase with an average student score of 83,33. Therefor, it could be concluded that problem solving method applying coulf increase student learning motivation at SD Negeri No 100724 Padang Lancat.